Us, Them, and Others in Management Research - Fitzsimmons, Stacey R. (Academy of Management Review, 2014)
The author responds to the article "Titles matter: Addressing the normalization of othering," by C.J. Vinkenburg in a 2014 issue of the journal regarding the use of the terms "they" or "them" in article titles within the "Academy of Management" publications. Topics discussed include the referral to multicultural employees as "they" in an article written by the author, whether the term "they" implies that individuals are members of an outgroup, and how authors can avoid othering in research articles. The author also discusses ways to mitigate the problem of othering in the context of management research..